Pediatric Life-Threatening Coronavirus Disease 2019 With Myocarditis. Issue 7 (July 2020) - Oberweis, Marie-Laure; Codreanu, Andrei; Boehm, Wolfgang; Olivier, Damien; Pierron, Charlotte; Tsobo, Chantal; Kohnen, Michel; Abdelrahman, Tamir T.; Nguyen, Nguyen T.; Wagner, Kerstin; de la Fuente Garcia, Isabel
Abstract : We report the case of a pediatric life-threatening coronavirus disease 2019 who presented as myocarditis with heart failure. Clinicians should be aware of this severe presentation of the disease in children, possibly linked to an exaggerated inflammatory host immune response to severe acute respiratory syndrome coronavirus 2.